Nevus anelasticus: how should such lesions be classified?. (26th March 2014) - Wang, Annie R.; Kent, Kathryn; Jagdeo, Jared; Robinson‐Bostom, Leslie; Bercovitch, Lionel
<x xml:space="preserve">Abstract</x> Nevus anelasticus represents a rare entity that is most commonly classified as a connective tissue nevus. It typically presents before 20 years of age with asymmetrically distributed white‐to‐skin‐toned or pink‐to‐red papules or plaques on the trunk and upper extremities. The lesion is defined histopathologically by the absence or degeneration of elastic fibers in the dermis. We report the case of a healthy 17‐year‐old female who presented with an asymptomatic slowly progressive plaque on the right inferior areola. Histopathologic examination showed the absence of elastic fibers in the papillary and upper reticular dermis and fragmented elastic tissue fibers in the deep reticular dermis. Although there is ongoing controversy regarding the nosology of this uncommon disorder, we propose that it is a distinct entity based on its histopathologic and clinical features.